A study of the forest and aquatic ecology of the Bitumen belt of Ogun state, Nigeria (Journal of Science and Technology, 2016)
A study of the forest and acquatic ecology of the bitumen belt of Ogun State, Nigeria was carried out. The status of the acquatic and wildlife species in the study area was investigated over a period of six months (January – June, 2005). The aim of the study was to identify and describe the type of wildlife and acquatic resources of the tar sand areas of Ogun State, Nigeria. The study was also carried out in order to identify some of the factors responsible for land cover and vegetation changes in the study area.Inventory of wildlife species was determined in the study area using a combination of methods like road count, variable transect belt, indirect indices, discussion with hunters and farmers, visits to bush meat processing centers and food vendors. The study shows that the aquatic environment of the study area is not very different from the aquatic environment in other parts of the rain forest region of Southern Nigeria. The impact of human activities was evident in the relative paucity of zooplankton and thelarger aquatic fauna. However, the surface water bodies were still relatively rich in phytoplankton, as a result of the enrichment of the water bodies by decayed vegetable matter from the forests. Also, the massive deforestation that has taken place and has continued unabated in the tar sands area did not portent well for aquatic life in the study area. The proposed mining of bitumen in the study area will further increase the rate of deforestation and of the generation of sediments which may silt up the waterchannels and reduce their biological productivity.